(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to review and analyze the scientific literature related to solar energy and innovation technology, by focusing on recent developments in solar energy technologies and the role of technological innovation in improving the efficiency of solar systems and enhancing their contribution to achieving sustainable development. The study employed a literature review methodology, compiling scientific studies from reliable databases and academic sources, including Google Scholar, Research Gate, Scribd, and local journals such as Shrouss Journal and the University of Sirte Journal of Humanities, in addition to specialized scientific articles and reports relevant to the research topic. The studies were analyzed and compared according to technical criteria. The review results showed that technological advancements in photovoltaic cells, concentrated solar power, storage systems, hybrid systems, and artificial intelligence technologies have significantly contributed to increasing the efficiency and reliability of solar energy production and reducing its costs. The studies also demonstrated that solar energy represents one of the most important sustainable alternatives to traditional energy sources, given its environmental and economic advantages, such as reducing carbon emissions and decreasing reliance on fossil fuels. Conversely, the review revealed the persistence of several challenges that limit the expansion of solar energy use. These include high initial investment costs, weak legislative and regulatory frameworks, limited supporting infrastructure, and the need to raise public awareness and enhance investment in research and development. The study emphasizes that achieving Maximizing the benefits of solar energy requires an integration of technological innovation, supportive policies, and a suitable investment environment, contributing to enhanced energy security and the achievement of sustainable development goals in the future.